Stepping Forward: Enhancing Cognitive Learning Outcomes through Hybrid RCCR-Based Learning on Circulatory System Material - Cicilia Sriliasta; Dewi Sri Surya Wuisan (Pandawan Sejahtera Indonesia, 2023)
The time constraints at the end of the semester often lead to suboptimal delivery of circulatory system materials, which consequently affect students' learning outcomes. Hence, this research aims to delve into the impact of applying the RCCR (Reflect-Collaborate-Convey-Record) approach based on Hybrid Learning on enhancing cognitive learning outcomes. This study utilizes a quasi-experimental design, encompassing a control group with pretests and posttests, though they are not equivalent. Evaluation of cognitive learning outcomes involves multiple-choice questions in both the pretest and posttest phases. The data from these evaluations are quantitatively analyzed in-depth. After the learning process, the average posttest score for the control group reached 71.61, while the experimental group achieved a score of 81.25. Statistical analysis indicates a significant difference in posttest results between the experimental and control groups. The analysis of change scores (N-gain) also shows a significant difference between the experimental and control groups (p<0.05). These findings highlight a strong connection between cognitive learning outcomes and metacognitive skills mastery (r=0.83). Consequently, this learning model presents a valuable alternative for overcoming classroom time constraints and effectively enhancing cognitive learning outcomes.